A 1984-Pixels, 1.26nW/Pixel Retinal Prosthesis Chip with Time-Domain In-Pixel Image Processing - Choi, Dong Hwi; Jee, Dong Woo (2022 IEEE Asian Solid-State Circuits Conference, A-SSCC 2022 - Proceedings, 2022)
The retinal prosthesis (RP) chip restores basic visual function in patients with retinal degenerative disease and improves patient's oriental skills and ability to localize objects. Since the RP chip has a low resolution due to a limited number of pixels, image processing such as edge-extraction is necessary to improve visual acuity [1]. The edge-extraction is also essential to generate power efficient stimulation patterns in the RP chip where heat generation due to power consumption should be minimized [2]. Since each pixel generates a photocurrent according to the intensity of the input light, the edge-extraction can be performed by directly processing photocurrents of neighboring pixels. However, current-domain analog processing requires multiple current branches for mirroring and consumes large static power [3-4]. Counter-assisted all digital processing with light-to-frequency converter demonstrates low power consumption for the edge processing, but it requires area-consuming multi-bit registers and large computational logic circuits [2]. In this paper, we propose a time-domain edge extraction technique for power and area-efficient in-pixel image processing for RP chips.
Keywords: Edge extraction; Images processing; Lower resolution; Pixel images; Power efficient; Retinal degenerative disease; Retinal prosthesis; Time domain; Visual acuity; Visual functions